Potential of a magnetic hybrid material produced using water hyacinth (Eichhornia crassipes) for removal of inorganic and organic pollutants from aqueous media - Lima, Jôse Raymara Alves; De Farias, Douglas Lira; Menezes, Thalles Henrique Santos; Oliveira, Rhayza Victoria Matos; Silva, Iris Amanda Alves; Da Costa Cunha, Graziele; Romão, Luciane Pimenta Cruz [UNESP] (Elsevier, 2020)
Investigation was made of the potential of in natura water hyacinth for use in the synthesis of a magnetic hybrid suitable for the removal of metals and pharmaceuticals from aqueous media. XRD and FTIR analyses confirmed that the synthesis method was effective in obtaining the hybrid (denoted AGMG). Assays to evaluate the influence of pH on the removal of copper, zinc, nickel, cobalt, and ibuprofen (IBP) showed higher removal percentages at pH4-5 for the metals and at pH 3 for IBP. The processes showed fast kinetics, with the removal rates in the first 5min exceeding 50% for the metals and 90% for IBP. The maximum AGMG adsorptive capacities (qmax, in mg g-1) were 18.3 for Cu(II), 10.1 for Zn(II), 7.33 for Ni(II), and 1.02mgg-1 for IBP. The following order of selectivity was obtained in tests employing mixed solutions of the three metals: Cu>Zn>Ni. The AGMG was reused in four cycles for the metals and in six cycles for IBP, with reuse efficiencies in the ranges 72-77% and 70-100%, respectively. The metal-saturated AGMG remaining after the reuse assays showed catalytic activity in the reduction of 4-nitrophenol with NaBH4 and could be reused in ten reduction cycles, with conversion rates from 89 to 100% and times from 21 to 26s.
Keywords: 4-nitrophenol; Ibuprofen; Magnetic hybrid; Metal; Remediation; Water hyacinth (Eichhornia crassipes)